Senam Hamil dan Penyuluhan Tanda-Tanda Persalinan Melalui Pelaksanaan Kelas Ibu Hamil di Kelurahan Sidanegara RT 02 RW 012 Kecamatan Cilacap Tengah Kabupaten Cilacap - Elifiya Elifiya; Marsela Amelia; Dianti Dianti; Frisca Dewi Yunadi; Tri Budiarti; Dhiah Dwi Kusumawati (Abdimas Indonesian Journal, 2022)
Pregnant women often experience many changes, both physical changes and psychological changes. Pregnancy exercises performed during pregnancy can help women focus on the labor process, prepare to tolerate pain, and convert stress and anxiety into energy. The purpose of this Community Midwifery Practice activity is to provide opportunities for pregnant women in Sidanegara Village to be precise on Rt 02 Rw 012, Central Cilacap District, Cilacap Regency. To understand the changes that occur during pregnancy and be able to prepare for the delivery process through Pregnancy Exercises. Sidanegara Village Precisely on Rt 02 Rw 012 Central Cilacap District, Cilacap Regency which was held on December 2, 2021. In this PKM, pregnant women received a positive response. Pregnant women seemed to be asking questions about the counseling provided and when participating in Pregnancy Exercises they seemed enthusiastic in the level of movement of the ability of pregnant women to do pregnancy exercise and the level of knowledge of the mother about the practice of pregnant exercise so that by carrying out this pregnancy exercise there is an increase in knowledge of pregnant women and the results of the increase after an evaluation of pregnant exercise are categorized as good, while the results l evaluation of counseling on signs of labor, i.e. pregnant women already know about the signs of labor